The Foundations of the Chinese Planned Economy - Howe, Christopher. author. aut Link
XIII, 370 p.
Keywords: A collection of documents concerning the foundations of the Chinese planned economy covering strategy and planning, industrial development and organization, agricultural development and population, and labour and urbanization.